Report of Panel of Experts on Reforms in Central Public Sector Enterprises (CPSEs) - Planning Commission (Planning Commission, 2011)
The report by the Planning Commission highlights the urgent need for reforms in Central Public Sector Enterprises (CPSEs) to enhance efficiency, competitiveness, and autonomy. Key recommendations include strengthening corporate governance through independent directors and specialized board committees, revamping HR policies for better manpower planning and performance-based compensation, and reforming the MOU system into tailored business performance frameworks. Technological capability and R&D are emphasized as crucial for sustaining competitiveness, with recommendations for increased investment, dedicated technology policies, IT planning, and institutional collaborations. The report also advocates for greater autonomy in forming joint ventures and partnerships, optimizing land use via a Public Sector Land Development Authority, and exploring a Single Holding Structure (SHS) for strategic management. Collectively, these reforms aim to transform CPSEs into innovative, accountable, and competitive enterprises, contributing meaningfully to India’s economic growth.
Planning Commission Government of India, New Delhi November 2011
Planning Commission Government of India, New Delhi November 2011
Keywords: CPSE Reforms; Corporate Governance; Human Resources; Technology; R&D; Public-Private Partnerships; Autonomy; Efficiency; Maharatna; Navratna